Application of the DDS PRO software for planning of bilateral sagittal split osteotomy of the mandible: clinical case description - Ya.E. Vares (Danylo Halytsky Lviv National Medical University, 2017)
Aim. Traditionally, one of the most important and precise parts of orthognatic interventions will always be planning. After this stage, the surgeon knows exactly which bones and in what way must be rebuilt to get the best result. Earlier, the conducting of a "virtual operation" was not possible. Everything has changed with the advent of the 3D scanners and printers and related software. Accordingly, the task of the study was to confirm the effectiveness of the application of virtual planning in general, and on the example of the application of specific software, in particular, 3D printing technologies in the execution of bilateral sagittal split osteotomy of the mandible, and to introduce this complex into routine surgical practice.